Simulation of Attractive Interaction Reaction for Binary Alloys - Al-Obaidy, Rahi Abid Hassan; Kahlol, Kadum K.; Ali, Fadul Husan (Nahrain University College of Engineering Journal, 2017)
In this research the attractive interaction reactions of binary alloy solidification have been simulated. A mean - field kinetic equations have been used in this investigation in order to simulate the crystal lattice of two metals of complete solid and liquid solubility ( compete miscibility ) with solid solution types. The simulation was conducted in a dimensionless method. The results showed that the maximum free energy f(p) decreased to the minimum level that is (-0.052) at (0.96) and (0.04)weight percentage concentration for the A and B metals respectively. On the other hand, the free energy increased until it reached its maximum level (-0.005) at a (0.5) concentration for both metals. Results also showed that the maximum free energy values gave a symmetrical trend before and after the concentration balance of the two metals used. A pseudo eutectic alloy has been formed at (0.5) concentration for the two metals at thermal energy level (KT) equal to (1). Also a symmetrical trend has been formed for concentration values of both metals before and after the eutectic alloy formation.